Role of Semi-quantitative Serum Procalcitonin in Assessing Prognosis of Community Acquired Bacterial Pneumonia Compared to PORT PSI, CURB-65 and CRB-65 - Lalita Fernandes; Akashdeep Singh Arora; Anthony Menezes Mesquita (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Community Acquired Pneumonia (CAP) is one of the commonest causes of patient’s visit to the Emergency Room (ER). Hospitalisation of patient depends on severity of pneumonia. Various pneumonia severity assessment scores are available to predict mortality in community acquired pneumonia but these scores are not commonly used. Procalcitonin is a biomarker which is raised in bacterial infection and is easy and quick to measure. The aim of our study was to assess the ability of baseline serum procalcitonin level to predict mortality of community acquired bacterial pneumonia compared to PSI, CURB-65 and CRB-65 and its add-on value to the simple CRB-65 score. Materials and Methods: Fifty five patients admitted with Community Acquired Bacterial Pneumonia were enrolled after taking informed consent and satisfying all inclusion and exclusion criteria. PSI, CURB -65, CRB-65 and PCT scores were determined on admission. PCT was measured by semi- quantitative assay; PCT Q. Primary outcome was 30 day mortality. Sensitivity, specificity, positive and negative predictive value of PCT for assessing mortality was calculated and compared to validated pneumonia severity scores; PSI, CURB-65 and CRB-65. We also assessed the ability of the combination of PCT to each of the scores to predict 30 day pneumonia specific mortality. Results: In receiver operating characteristic analysis for mortality prediction, area under curve (95% CI) for PCT, PSI, CURB-65 and CRB-65 was 0.92 (0.85, 1.0), 0.88 (0.78, 0.98), 0.88 (0.76, 0.99), 0.9 (0.78, 1.0) respectively. Combination of PCT to each of the scores improved the prognostic ability to predict 30 day pneumonia specific mortality. Conclusion: Semi-quantitative PCT level at admission is an excellent test to predict the outcome of pneumonia. It predicts patients at low risk of mortality from community acquired bacterial pneumonia.